2019
DOI: 10.3846/jbem.2019.9602
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capacity, Business Sophistication and Macroeconomic Stability: Empirical Evidence From Oecd Countries

Abstract: The main aim of this study is to explore the linkages between innovation capacity, business sophistication, and macroeconomic stability within OECD countries. In order to obtain information regarding the relationship between time series variables, the Pedroni cointegration, Kao cointegration, fully modified ordinary least square, dynamic ordinary least square, Granger causality, and Dumitrescu Hurlin causality tests are employed. The empirical results reveal that improvement in business sophistication triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In the current era of globalization, investing in a more knowledgeable workforce and management of this knowledge (Hassan & Raziq, 2019) gives businesses a competitive advantage in terms of innovation. According to Kirikkaleli & Ozun (2019), in innovation-driven economies, business sophistication and innovation are seen as the essential components of competitiveness.…”
Section: Business Sophistication and Innovation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the current era of globalization, investing in a more knowledgeable workforce and management of this knowledge (Hassan & Raziq, 2019) gives businesses a competitive advantage in terms of innovation. According to Kirikkaleli & Ozun (2019), in innovation-driven economies, business sophistication and innovation are seen as the essential components of competitiveness.…”
Section: Business Sophistication and Innovation Performancementioning
confidence: 99%
“…Additionally, the interconnection of businesses with government and research institutions and customers have been termed as the most signi cant linkages that boost innovation (Ortega & Serna, 2020). A study by Kirikkaleli & Ozun (2019) found a positive link between business sophistication and innovation capacity in OECD countries.…”
Section: Business Sophistication and Innovation Performancementioning
confidence: 99%
“…Kirikkaleli and Ozun [25] explored the linkages between innovation capacity, business sophistication, and macroeconomic stability within OECD (Organization for Economic Cooperation and Development) countries, and found innovation capacity positively leads to advanced business sophistication. Carlos et al [26] compared the innovation output indicators of Spanish knowledge-intensive service firms with those of other categories of non-knowledge-intensive service firms and manufacturing firms, found the main determinants of innovation output are the following: cooperation with other partners to innovate, R&D intensity, and the size of the firm. Wei and Chan [27] found the cooperative stability of China’s satellite industry military-civilian collaborative innovation was positively related to the cooperation revenue, liquidated damages, and government incentives, and negatively related to basic income, R&D costs, information communication costs, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the scientists in the papers [18][19][20][21][22][23] proved the linking between innovations, sustainable business model and country's competitiveness. The scientists in the papers [24][25][26][27][28][29] proved that sustainable business model could not be realised without innovations. The results of the analysis showed that the scientists analysed sustainable business model from the environmental, economic and social point of views.…”
Section: Introductionmentioning
confidence: 99%